Case studies from elite youth soccer: Reflections on talent development practices - Wixey, D.; Ryom, K.; Kingston, K. (International Sport Coaching Journal, 2021)
With early specialisation being commonplace within elite youth soccer, knowledge of the psychosocial implications associated with talent development practices would be of considerable use for the coaching practitioner. This paper uses case studies as a platform to discuss potential psychosocial implications of early specialisation, and further, it also offers practical suggestions for the elite youth soccer coach. Three case studies were chosen; each is an account of observations that took place within a British soccer academy. Themes of the case studies included adult-led structures in early specialisation, awareness of need thwarting coach behaviours, and the retention or release of players. The case studies were deliberately chosen to prompt discussion, reflection, and action. Following the presentation of each case study, a theoretically driven discussion is formulated. Practical suggestions are then provided to assist in the management of talent development practices within elite youth soccer and to further enrich the experiences of players. Concluding thoughts and areas for future research are briefly discussed.